Implementasi Perancangan Interior Restoran dan Toko Oleh-Oleh Trijaya Di Tabanan Bali - Sucipto, Gabriella Yoan; Kusumowidagdo, Astrid; Indrawan, Stephanus Evert (KREASI, 2016)
This business offers services that are related to interior design for housing and other commercial area. G.Yo Interior consultant put innovation and relationship with all clients as a priority in order to produce highest customer satisfaction and eventually solving all problems. This paper focuses on the big picture of the restaurant and other important aspects that needs to be highlighted in the case of designing a restaurant. The design must meet its client’s needs and wants in designing a restaurant. All other aspects will be investigated further by the use of materials and space allocation, based on how the design should be done in order to achieve the standard required.